Diagnosis and treatment of arterial stiffness, pulmonary hypertension, diastolic cardiac dysfunction against the background of ischaemic heart disease in comorbid patients - Nadezhda N. Pribylova; Kristina O. Leonidova; Vladislav S. Pribylov; Evgeny A. Shabanov; Sergey A. Pribylov; Nikita V. Novikov (Research Results in Pharmacology)
Introduction: In the context of cardiology and neurology, special attention is paid to the problems of cardiovascular and cerebrovascular pathologies, often caused by vascular dysfunction. Haemodynamic parameters, in particular arterial stiffness (AS), and epicardial fat thickness (EFT), play a significant role in the assessment of cardiovascular health. The aim of the study was to evaluate the correlation between arterial stiffness, pulmonary hypertension (PH), epicardial fat thickness and diastolic myocardial dysfunction in comorbid patients.